Major patterns of group interaction in South African society - Savage, Michael (My University, 1974)
Although recent historians have stated "the central theme of South African history is interaction between peoples of diverse origins, languages, technologies, Ideologies and social systems, meeting on South African soil", scant attention has been paid to such interaction by social scientists. Instead, most work in such disciplines has been segmentary, and focuses on the Internal arrangements or attitudes of one group rather than on the relationships that that group has to other groups or to the wider society. This in itself may be one reflection of the polarities of the society that have influenced the pattern of social research itself. The result however, is that outside of the work of historians, there has been insufficient study of the consequences of interaction between the different groups in the population. Yet, such interaction is one vital key to an understanding of the social structure. In this paper, an attempt will be made to overview the most important patterns of group interaction across the lines - ( political, ethnic, economic and class - that so clearly demarcate the major groups in South African society. The primary focus in this exploration of the contact and cleavages between such groups will be the present, with some attempt to indicate emerging trends.
African Studies Seminar series. Paper presented March 1974
Keywords: South Africa. Race relations; South Africa. Social conditions; South Africa. Politics and government